Factors Affecting Technical Efficiency to Optimize Cassava Production in Drylands - Roidah, Ida Syamsu; Rizkiyah, Noor; Rozci, Fatchur; Faisal, Herry Nur (Jurnal AGRISEP, 2025)
Improving the technical efficiency of cassava is essential, as it enhances resource use, boosts, and drives broader economic growth. This study aimed to estimate the technical efficiency of cassava production as a contribution to food security, job creation, and sustainable agriculture-based development. Trenggalek Regency was chosen as the research location, considering that the regency is in the centre of cassava production in East Java Province, as a key factor in achieving sustainable agricultural development. The data were obtained through interviews with 70 cassava farmers, selected using stratified random sampling across two sub-districts. The data used in this study were primary and secondary data, while the data analysis used the stochastic frontier production function. The results of the study on the efficiency of production factors include land area (89.31), cassava seeds (5.36), labour (34.20), NPK fertiliser (6.70), KCL fertiliser (0.69), SP36 fertiliser (0.51), urea fertiliser (-0.49), and pesticide (-0.09). In general, cassava farming in Trenggalek Regency is not technically efficient in utilising production factors. In fact, technical efficiency is an important factor that needs to be considered, and there is great potential to increase cassava production through efficiency improvements. Therefore, interventions are needed to improve the technical efficiency of cassava farming through intensive counselling and training programs, appropriate input use, technological development, and improved access to capital, aiming to positively impact farmers` income, food security, and sustainable agricultural development.